ANALYSIS OF CLEAN AND HEALTHY LIVING BEHAVIOR IN ELEMENTARY SCHOOLS - Memo Harry Sandra; Maksuk, Maksuk; Ferly Oktriyedi (Indonesia Epidemiological Journal, 2025)
Background: Clean and Healthy Living Behaviors remain a problem, especially among elementary school children. This study aims to analyze clean and healthy living behaviors among elementary school children. Methods: This research is an analytical observational study with a cross-sectional design. Data were collected using a questionnaire through student interviews. Then, they were analyzed univariately, bivariately using the chi-square test, and multivariately using multiple logistic regression. Results: The research results showed that knowledge, facilities and infrastructure, information exposure, and the role of teachers and staff were good, but the majority of attitudes remained negative. All of these variables were significantly correlated, with two variables being the most dominant in determining Clean and Healthy Living Behavior: knowledge and facilities and infrastructure. Conclusion: Clean and Healthy Living Behavior is significantly related to knowledge, attitudes, facilities and infrastructure, exposure to information, the role of teachers and the role of officers.